Hotter days, smaller ranges: Air temperature constrains livestock movement and space use in Mediterranean rangelands - Lara Naves-Alegre; Roberto Pascual-Rico; José Antonio Sánchez-Zapata; Antonio Contreras; Marina Rincón-Madroñero; Jose Manuel Zamora-Marín; Jomar M. Barbosa (Journal of Environmental Management, 2026)

Public management attitudes and behavioural intentions towards the management of (over)abundant wild ungulate populations - Antonio J. Carpio; Roberto Pascual-Rico; Tamara Murillo-Jiménez; María Martínez-Jauregui; Rafael Villafuerte-Jordán; Pelayo Acevedo (Ambio, 2026)
Social perceptions of wild ungulates depend on their abundance and the socioeconomic context. These perceptions shape attitudes toward management and explain social behavior toward the species. Our objective was to evaluate attitudes and behavioral intentions toward wild ungulate management in the Iberian Peninsula. We conducted a survey of 440 participants in mainland Spain. Respondents generally supported non-lethal methods, though attitudes varied with socioeconomic context. A key finding was that attitudes did not directly translate into behavioral intentions, suggesting the influence of cognitive dissonance or social norms. While many respondents supported education and awareness actions, a considerable share reported no intention to participate or provide financial support. Recreational hunting was broadly rejected. Notably, hunters’ involvement in management was associated with attitudes that more strongly predicted behavioral intentions. These results highlight the complexity of the social landscape and underscore the need to adapt management strategies to socioeconomic settings and behavioral drivers.

A necessary clarification about interspecific competition in ecology and the invasiveness of the exotic aoudad: Comment on Cassinello et al. 2025 - Roberto Pascual-Rico; Francisco Botella (Biological Conservation, 2026)

Different objective, same mechanism, and unforeseen consequences: Insights into a pioneering species introduction for conservation - Roberto Pascual-Rico (Biological Conservation, 2025)

A sarcoptic mange outbreak drives long-term patterns of a fitness trait in an exotic ungulate - Roberto Pascual-Rico; José A. Sánchez-Zapata; Mónica G. Candela; Sergio Eguía; Jomar M. Barbosa (European Journal of Wildlife Research, 2024)
Species phenotypes are driven by persistent selective pressures that condition their adaptation to the environment. However, stochastic critical events, such as disease outbreaks, may also act as selective pressures because of drastic population decline. External structures like horns of ungulate species may reflect the consequences of these selective pressures on animal fitness. Using a generalized linear model approach, we analysed how a massive mortality event caused by a sarcoptic mange outbreak in 1992 affected the horn size of an Iberian aoudad population (dataset from 1980 to 2014) by comparing horn length before and after the outbreak. We found that this episodic, albeit massive, outbreak changed long-term trends in age-size horn relations. Both females and males presented shorter horns after the sarcoptic mange outbreak, although more marked in males. Even when animals reached mature ages, horn length did not increase with age to the same degree as before the outbreak. We consider that two processes may have acted on the population: a bottleneck favoured “shorter horns” phenotype and a post-mange enzootic period limited horn growth, as infected animals may invest more resources in the immune system. Overall, our results show a top-down regulation of a fitness trait for an ungulate population mediated by a parasite. This disease outbreak showed long-lasting effects on the ungulate population, with ecological and management implications. Graphical Abstract

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

The prohibition of recreational hunting of wild ungulates in Spanish National Parks: Challenges and opportunities - Antonio J. Carpio; Eduardo Laguna; Roberto Pascual-Rico; María Martínez-Jauregui; José Guerrero-Casado; Joaquín Vicente; Ramón C. Soriguer; Pelayo Acevedo (Science of The Total Environment, 2024)

The underestimated role of carrion in vertebrates' diet studies - Esther Sebastián‐González; Jon Morant; Marcos Moleón; Daniel Redondo‐Gómez; Zebensui Morales‐Reyes; Roberto Pascual‐Rico; Juan Manuel Pérez‐García; Eneko Arrondo (Global Ecology and Biogeography, 2023)
Aim Despite the increasing scientific evidence on the importance of carrion in the ecology and evolution of many vertebrates, scavenging is still barely considered in diet studies. Here, we draw attention to how scientific literature has underestimated the role of vertebrates as scavengers, identifying the ecological traits that characterize those species whose role as scavengers could have gone especially unnoticed. Location Global. Time Period 1938–2022. Major Taxa Studied Terrestrial vertebrate scavengers. Methods We analysed and compared (a) the largest database available on scavenging patterns by carrion‐consuming vertebrates, (b) 908 diet studies about 156 scavenger species and (c) one of the most complete databases on bird and mammal diets ( Elton Traits database). For each of these 156 species, we calculated their scavenging degree (i.e. proportion of carcases where the species is detected consuming carrion) as a proxy for carrion consumption, and related their ecological traits with the probability of being identified as scavengers in diet studies and in the Elton Traits database. Results More than half of the species identified as scavengers at monitored carcasses were not assigned carrion as food source in their diet studies nor in the Elton Traits database. Using a subset of study sites, we found a direct relationship between a species' scavenging degree and its rate of carrion biomass removal. In addition, scavenger species, which were classified as non‐predators and mammals had a lower probability of being identified as scavengers in diet studies and in the Elton Traits database, respectively. Main Conclusions Our results clearly indicate an underestimation of the role of scavenging in vertebrate food webs. Given that detritus recycling is fundamental to ecosystem functioning, we encourage further recognition and investigation of the role of carrion as a food resource for vertebrates, especially for non‐predator species and mammals with higher scavenging degree .

The value of transhumance for biodiversity conservation: Vulture foraging in relation to livestock movements - Natividad Aguilera-Alcalá; Eneko Arrondo; Roberto Pascual-Rico; Zebensui Morales-Reyes; José M. Gil-Sánchez; José A. Donázar; Marcos Moleón; José A. Sánchez-Zapata (Ambio, 2022)
In recent decades, intensive techniques of livestock raising have flourished, which has largely replaced traditional farming practices such as transhumance. These changes may have affected scavengers’ behaviour and ecology, as extensive livestock is a key source of carrion. This study evaluates the spatial responses of avian scavengers to the seasonal movements of transhumant herds in south-eastern Spain. We surveyed the abundance of avian scavengers and ungulates, and analysed the factors affecting the space use by 30 GPS-tracked griffon vultures ( Gyps fulvus ). Griffons’ foraging activity increased in the pasturelands occupied by transhumant herds, which implied greater vulture abundance at the landscape level during the livestock season. In contrast, facultative scavengers were more abundant without transhumant livestock herds, and the abundance of wild ungulates did not change in relation to livestock presence. We conclude that fostering transhumance and other traditional farming systems, to the detriment of farming intensification, could favour vulture conservation.

Ungulates Attenuate the Response of Mediterranean Mountain Vegetation to Climate Oscillations - Jomar Magalhães Barbosa; Roberto Pascual-Rico; Sergio Eguia Martínez; José A. Sánchez-Zapata (Ecosystems, 2020)

Ecological niche overlap between co-occurring native and exotic ungulates: insights for a conservation conflict - Roberto Pascual-Rico; José Antonio Sánchez-Zapata; Joan Navarro; Sergio Eguía; José Daniel Anadón; Francisco Botella (Biological Invasions, 2020)

Is diversionary feeding a useful tool to avoid human-ungulate conflicts? A case study with the aoudad - Roberto Pascual-Rico; Juan Manuel Pérez-García; Esther Sebastián-González; Francisco Botella; Andrés Giménez; Sergio Eguía; José Antonio Sánchez-Zapata (European Journal of Wildlife Research, 2018)